Modeling and Simulation of Frontal Crash Between Heavyweight and Lightweight Vehicles - ibrahim, mohd norihan; Murali, Vivekananta (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This represent on the simulation of a frontal collision between a light and heavy weight vehicle by using ANSYS software. The study is focusing on the deformation and crashworthiness behaviour of frontal crash impact of both vehicles. The material for the vehicles is aluminium alloy and structural steel. Based on the result generated by the simulation, the maximum deformation occurs on lightweight vehicles compared with heavyweight vehicle. The maximum equivalent stress generated by the collision between both vehicles. The maximum stress occurred on the car body where it shows the force exerted on car is higher compare to the lorry body. Therefore, after the collision the car will face large damage as compared to heavyweight vehicle or lorry. The lightweight vehicle faced the most damage compare the other. Besides, the stress generated on the car body was the highest